2006
DOI: 10.1177/002204260603600407
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Socio-Cultural Factors Contributing to Prescription Drug Misuse among College Students

Abstract: Although recent increases in collegiate prescription drug misuse have generated a great deal of concern, there are few analyses available that examine the socio-cultural factors influencing these trends. This article attempts to address this gap in knowledge by providing an analysis of several socio-cultural factors influencing pharmaceutical misuse by college students. Prescription drugs are put to a number of different purposes in the collegiate setting, including self-medication, socio-recreation, and acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 23 publications
5
74
0
Order By: Relevance
“…In particular, educational programs need to focus on the cultural norms that permit a "time-out" for students. 29 As noted by Quintero and colleagues, their exploratory and qualitative research has demonstrated the importance of placing nonmedical prescription drug use within the larger sociocultural context. 29,37 This problematic "time-out" culture that is pervasive on college campuses facilitates drug use, abuse, and experimentation among undergraduate students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, educational programs need to focus on the cultural norms that permit a "time-out" for students. 29 As noted by Quintero and colleagues, their exploratory and qualitative research has demonstrated the importance of placing nonmedical prescription drug use within the larger sociocultural context. 29,37 This problematic "time-out" culture that is pervasive on college campuses facilitates drug use, abuse, and experimentation among undergraduate students.…”
Section: Discussionmentioning
confidence: 99%
“…29,37 This problematic "time-out" culture that is pervasive on college campuses facilitates drug use, abuse, and experimentation among undergraduate students. 29 One could view prescription drugs as simply the new kid on the block, and although we are aware that prescription drugs pose a unique problem because of their easy accessibility and the misperception that they are safer than other illicit drugs (ie, cocaine), it is important to consider that the use of nonmedical prescription drugs among students has been incorporated into the drug culture.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative studies have reported motivations for misuse that include general reasons (e.g., to get high), and reasons linked to specific types of prescription drugs, such as opioids to relieve pain, tranquilizers to decrease anxiety, or stimulants to increase alertness (Boyd, McCabe, Cranford, & Young, 2006; McCabe, Boyd, &Teter, 2009; McCabe, Cranford, Boyd, & Teter, 2007; McCabe, Teter, & Boyd, 2005). Moreover, qualitative studies have reported social motives, for example, to facilitate social interactions and activities (Quintero, 2009b), and quasi-medical or self-medication motives, for example, to relax/relieve tension and to moderate the negative effects of other substances (Bardhi, Sifaneck, Johnson, & Dunlap, 2007; Hunt, Bailey, Evans, & Moloney, 2009; Quintero, Peterson, & Young, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…OP: Reformulation of OxyContin that utilizes physical and chemical barriers to make tablets difficult to manipulate for misuse. Prescription drug misuse: The use of prescribed drugs without a prescription or against a licensed medical provider's directions (Quintero, Peterson & Young, 2006). Prescription opioids: Prescribed by a licensed medical provider to relieve pain and includes such pharmaceuticals as hydrocodone (e.g.…”
Section: Glossarymentioning
confidence: 99%